Why doesn't biodiversity monitoring support conservation priorities in the tropics? - Sheil, Douglas (2002)
Biodiversity monitoring activities can hinder rather than promote conservation in tropical countries.The national institutions responsible for conservation in developing countries have very limited resources, which given donors and richer agencies scope for considerable influence. However, those nominally concerned with supporting conservation often overlook the practicalities. As a result, many initiatives divert scarce resources away from fundamental management priorities. This article addresses the importance of various types of biodiversity monitoring, suggests practical biodiversity conservation priorities and indicates how external agencies can deflect local management from addressing these. The article is an elaboration of opinions published recently (Sheil, 2001), based mainly on author's personal experiences in Africa and South-east Asia. One vital step to addressing the problem is a frank discussion of how conservation goals should be supported.